Affordable green roof system for middle income households - Nesan, L. Jawahar; Mohammed, Abdul Hakim (CRES, FKSG, 2006)
This paper presents a green roof system suitable for middle-income households in Pakistan. While the west has successfully implemented green building systems, the developing countries did not realise it mainly due to the lack of affordable systems and technical know how and the presence of social barriers. Especially, in these countries, the energy efficient building envelope is beyond the reach of the middle-income households, as they cannot afford the current systems. A new system has been developed with respect to the specific needs of the middle class dwellings in the city of Lahore. A detailed survey was conducted among the middle-income households in the Wahdat Colony (Lahore, Pakistan) to assess both the specific constraints and needs of the green roof system. Several aspects including the building envelope, roofing system, local materials, use of air conditioners, local weather, thermal comfortability, thermal response of the existing residential buildings, health problems, and sleeping patterns influenced by the solar radiations were studied and properly addressed in the model development. The new system was designed by using locally available materials and to meet the specific demands of the middle-income residents including affordability and less maintenance. Cost efficiency of the new system has been analysed and found more advantageous than the use of present insulated roof systems and air conditioners.